METODE CONDITIONAL AUTOREGRESSIVE DALAM ANALISIS PENYEBARAN KASUS PENYAKIT TUBERCULOSIS - RAJAK, SANDIKA S.; ISMAIL, SUMARNO; RESMAWAN, RESMAWAN (Department of Mathematics, Universitas Negeri Gorontalo, 2021)
This research discusses the use of CAR model in finding out factors that significantly influence TBC transmission and figuring out its transmission patterns in Gorontalo city. The methods apply CAR model aiming to discover factors that significantly influence TBC transmission and Moran's Index aiming to identify its transmission pattern Findings reveal that the number of impoverished population and highlands in Gorontalo city are factors that significantly influence disease transmission The transmission patterns also indicate positive spatial autocorrelation that signifies a similar category among sub-districts